Pelayanan siswa yang melanggar tata tertib sekolah (studi pada siswa SMP Negeri Kota Banda Aceh) - Desi Ulan Dari; Martunis Yahya; Said Nurdin (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2019)
Counseling services for student who violate school discipline will help students to be more disciplined. This research was conducted to find out the types of problems in violating school rules, student services that violate school rules and the obstacles encountered by BK teachers in carrying out case services in dealing with students who violate school rules. The approach used in this research is a qualitative approach with descriptive methods. The locations of this research are SMP Negeri 2, SMP Negeri 4 and SMP Negeri 8 Kota Banda Aceh. Data collection techniques used were interviews and documentation. The results showed that the school rules violations that were still carried out repeatedly by students in the Banda Aceh City Middle School were smoking, ditching, fighting, and carrying cellphones (playing online games). In handling cases of disciplinary violations in schools, counseling teachers handle problems through the stages of understanding the description of the problem, studying the background and foreground of the problem by collecting a number of data, making efforts to prevent and solve problems, as well as involving relevant parties. Obstacles experienced are, BK teachers are less able to adjust the time with parents and school principals, less able to understand student characters, parents' greetings when visiting home are sometimes not good, lack of parent collaboration with BK teachers, subject teachers lack understanding with respect to their respective responsibilities, subject teachers deal with students' problems without cooperating with homeroom teachers and counseling teachers, and school principals lack collaboration with related parties (such as the health department, religious department, and police) in carrying out guidance and counseling activities .Keywords: Violations of School Rules, Service Problems, Service Obstacles Problems Abstrak: Pelayanan bagi siswa yang melanggar tata tertib sekolah akan membantu siswa agar lebih disiplin. Penelitian ini dilakukan untuk mengetahui jenis-jenis masalah pelanggaran tata tertib sekolah, pelayanan siswa yang melanggar tata tertib sekolah serta hambatan-hambatan yang dijumpai guru BK dalam melaksanakan pelayanan kasus dalam menangani siswa yang melanggar tata tertib sekolah. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan metode deskriptif. Lokasi penelitian ini adalah SMP Negeri 2, SMP Negeri 4, dan SMP Negeri 8 Kota Banda Aceh. Teknik pengumpulan data yang digunakan adalah wawancara dan dokumentasi. Hasil penelitian menunjukan bahwa pelanggaran tata tertib sekolah yang masih dilakukan berulang kali oleh siswa di SMP Negeri Kota Banda Aceh yaitu, merokok, membolos, berkelahi, dan membawa HP (bermain game online). Dalam menangani kasus pelanggaran tata tertib di sekolah, guru BK menangani permasalahan melalui tahap memahami gambaran masalah, mempelajari latar belakang dan latar depan masalah dengan pengumpulan sejumlah data, melakukan usaha pencegahan dan pemecahan masalah, serta melibatkan pihak-pihak yang terkait. Hambatan yang dialami yaitu,  guru BK kurang mampu menyesuaikan waktu dengan orangtua siswa dan kepala sekolah, kurang mampu memahami karakter siswa, sambutan orangtua siswa pada saat melakukan kunjungan rumah kadang-kadang kurang baik, kurangnya kerjasama orangtua dengan guru BK, guru mata pelajaran kurang paham terhadap tanggung jawabnya masing-masing, guru mata pelajaran menangani masalah siswa tanpa bekerjasama dengan wali kelas dan guru BK, dan kepala sekolah kurang bekerjasama dengan pihak-pihak terkait (seperti, dinas kesehatan, departemen agama, dan kepolisian) dalam pelaksanaan kegiatan bimbingan dan konseling.Kata Kunci: Pelanggaran Tata Tertib Sekolah, Pelayanan Masalah, Hambatan Pelayanan Masalah